Perceptions of Portibi District Religious Affairs Office Employees Regarding Population Administration in Unregistered Marriages - Siregar, Masdelina (Jurnal El-Thawalib, 2025)
Unlawful marriages that do not follow official procedures at the Office of Religious Affairs (KUA) are still common in the Portibi District. This practice creates obstacles in issuing Family Cards (KK) and creates legal uncertainty for couples and family members. A lack of understanding of legal procedures is a major contributing factor. This study aims to analyze the perceptions of Marriage Registrars at the Portibi District KUA regarding the issuance of KKs for couples who marry unlawfully. This research employs a descriptive qualitative approach. Primary data were obtained from employees of the KUA Portibi Subdistrict, while secondary data were collected from books, journals, government publications, observations, and document studies. Data analysis was conducted through data reduction, data presentation, and inductive conclusion drawing. The findings reveal that most KUA employees in Portibi perceive population administration as a fundamental aspect of marriage implementation in accordance with existing laws and regulations. They believe that unregistered marriages create various adverse consequences, such as difficulties in recording the birth of children, obtaining population documents, and accessing the legal rights of spouses and children. However, employees also recognize that social, economic, and cultural barriers continue to contribute to the persistence of unregistered marriages among specific segments of the community. The study concludes that the perceptions of KUA Portibi employees are generally consistent with current regulations, emphasizing the importance of marriage registration as part of the population administrative order and legal protection for citizens. These findings are expected to serve as a foundation for improving public awareness and education about the importance of marriage registration, as well as for strengthening KUA's role in enforcing population administration policies.